ANALISIS NPL DAN LDR TERHADAP ROA PADA PT BANK MANDIRI Tbk, PT BANK NASIONAL INDONESIA Tbk DAN PT BANK RAKYAT INDONESIA Tbk - hartanti hartanti (Universitas Bina Sarana Informatika, 2017)
The financial statements can be used to measure the financial performance of banks, financial statements can be calculated financial ratios that may be considered in making a decision. The objective of this study was to determine the relationship and influence simultaneously or partially NPL, LDR and ROA at three banks, namely PT Persero. Bank Mandiri Tbk, the National Bank and Bank Rakyat Indonesia Tbk Indonesia Tbk. The data used in the financial statements of the 1st quarter of 2011- the third quarter of 2015 before the bank obtained a loan from Bank of China. The research method using quantitative analysis method to analyze the relationship and the influence of dependent and independent variables either simultaneously or partially. As for the independent variable in this study NPL (X1), LDR (X2) and ROA Dependent Variable (Y). The data were processed using SPSS Version 20. In this study using multiple linear regression analysis. The results showed no significance relationship between the NPL (x1) and ROA (Y) and the relationship is weak and negative; no significance relationship between LDR (x2) and ROA (Y) and the relationship is weak and positive (unidirectional); NPL (x1), LDR (x2) together affect significantly the ROA (Y); Partially NPL (x1) negative effect on ROA (Y); While LDR (x2) has no effect on ROA (Y). should be further enhanced both in terms of its financial performance and LDRnya NPL and control over the invested assets that do not arise problem loans. Key words : NPL; LDR; ROA